T315I-mutated myeloid sarcoma. (2019) - Zhang, Yumeng; Swoboda, David M.; Grover, Aditya; Nodzon, Lisa; Zhang, Ling; Pinilla-Ibarz, Javier
Abstract: Myeloid Sarcoma (MS) is diagnosed by an extramedullary proliferation of immature granulocytic cells. Its association with chronic myeloid leukemia (CML) is rare. CML is characterized by BCR-ABL1 gene rearrangement and therapies with tyrosine kinase inhibitors (TKI) are very effective. However, TKI resistance may occur secondary to the development of ABL1 mutations. T315I is a common mutation that accounts for ∼20% clinical resistance to TKIs. We report the first case of a patient with T315I mutated myeloid sarcoma that occurred after complete cytogenetic response with dasatinib of a chronic phase CML. The patient was successfully treated with induction chemotherapy and ponatinib.